Two-Dimensional Videos to Improve Listening Skills for Fiction Stories in Elementary Schools - Fadloil, Wahid Ulil; Sismulyasih, Nugraheti (JOLLT Journal of Languages and Language Teaching, 2024)
Media plays a crucial role in the learning process, and continuous innovation in media usage is essential to sustain student engagement. This study aims to develop a two-dimensional video using the Animaker platform to enhance elementary students’ listening skills. The video, designed as a learning tool, was evaluated for its practicality, validity, and effectiveness. The research utilized the Research and Development (RnD) method to achieve this objective. The study’s findings indicate that the media is highly feasible for use. This is supported by the product feasibility test results, which showed an 85.71% approval rating from media experts and a 92.18% approval rating from material experts. The practicality of the media was also affirmed through student and teacher response questionnaires, which averaged a 96.18% approval rating. Additionally, the N-Gain test results demonstrated moderate improvements, with scores of 0.5083 in the small-scale test and 0.6082 in the large-scale test. Based on the findings, the study concludes that the use of two-dimensional video media developed with the Animaker application significantly improves elementary students’ listening skills in fiction stories. The high feasibility, practicality, and moderate effectiveness ratings suggest that this innovative media tool is a valuable asset in the educational process, successfully engaging students and enhancing their listening abilities.